FAKTOR YANG BERPERAN TERHADAP DEPRESI, KECEMASAN DAN STRES PADA PENDERITA DIABETES MELITUS TIPE 2: STUDI KASUS PUSKESMAS KECAMATAN GAMBIR JAKARTA PUSAT - Lusiana Bintang Siregar; Lidia Laksana Hidajat (MANASA, 2017)
Increasing number of Diabetes Mellitus type 2 patient needs to be noticed to psychological aspects that engage on the patient’s care and recovery. The aim of this research is to know the factors of depression, anxiety, and stress on Diabetes Mellitus type 2 patients at Puskesmas Kecamatan Gambir Jakarta Pusat. In the research process, partisipants are given Depression Anxiety Stress Scale (DASS), for picturing their depression, anxiety, and stress. This research involves 5 Diabetes Mellitus patient to be the participant. The DASS of 5 partisipants show that they have high depression score. After DASS, we interviewed those participant to know the factors of depression, anxiety, and stress. From the interview, we know that cognitive, illness duration, personality, and economic factor may influence the Diabetes Mellitus type 2 patients. From this finding, we design an intervention, such as group counseling, creating support group, and relaxation. Group counseling can be used as a tool to have a support group.